Assessment practices in the developing world: predictors of assessment practices in Ugandan institutions of higher learning - Matuvo, Musa; Zubairi, Ainol Madziah (IIUM Press, 2015)
This study analysed the predictors of assessment practices employed by faculty at selected institutions in Uganda. An Assessment Practices Inventory Modified (APIM) scale was distributed to a sample of 350 academic staff selected from both private and public universities in Uganda. Random sampling was used to select the participants for this study. MANOVA and multiple regression analysis were employed for data analysis. Differences were revealed in faculty assessment practices according to their academic levels and specialisations, and not in the type of universities. Differences in academic levels cut across all the assessment practices sub-scales (design, administration, interpretation, and application) while in specialisations differences were only in assessment interpretation. It was also found out that academic levels and formal assessment course undertaken are the only significant predictors of the academic staff’s assessment practices among the many hypothesised predictors (type of universities, specialisations, academic levels, class size, and assessment course). Generally, from the descriptive results of this study it has been noted that academic staff in Ugandan universities lack appropriate assessment skills in assessing their students. This has led to a recommendation that formal assessment training programmes should be made mandatory to all academic staff in universities in Uganda in order to improve their assessment skills to ensure quality in the way they assess students.